Prevalence and factors associated with physical punishment and psychological aggression towards children in Laos: Results of the 2017 social indicator survey - Supa Pengpid (2022)
Background: Physical and psychological child punishment is an important public health problem. Objectives: This study aimed to assess the prevalence and factors associated with physical punishment and psychological aggression toward children (1 - 14 years of age) in Laos. Methods: In the nationally representative 2017 Lao Social Indicator Survey, 20,949 mothers or caretakers of children aged 1 - 14 years responded to questions on child disciplining methods used by adults in households during the past month and attitudes toward violence. Logistic regression was used to investigate the association between household and maternal characteristics and physical punishment and psychological aggression toward children. Results: The prevalence of psychological aggression was 64.0% (shouted, etc., 60.5% and called child dumb, etc., 26.4%), the prevalence of any physical punishment was 35.6% (spanked, etc., 27.1%, hit on extremities 23.9%, hit on the bottom, etc., 4.9%, hit on face 3.9%, and “beat the child as hard as one could” 1.0%). In adjusted logistic regression analysis, male gender, poorer household wealth status, living in the central and southern region of the country, the child living with biological parents, agreement with physical punishment of children were positively, while older age, urban residence, and belonging to the Lao-Tai ethnolinguistic group were negatively associated with any physical punishment. Older age, male gender, living in the central region of the country, the child living with biological parents, and agreement with physical punishment of children were positive, whereas rural residence without road and living in the southern region of the country were negatively associated with psychological aggression. Conclusions: Psychological aggression and, to a lesser extent, physical punishment of children are common in Laos. Interventions to prevent psychological aggression and physical punishment towards children should support parents in adapting non-violent forms of parenting practices.